INFLUENCE OF FOOT TYPE ON BALANCE AND POSTURAL SWAY AMONG THE COMMUNITY DWELLING OLDER ADULTSâ€ - NAIDU RAJESWARI GOPAL; KIRUTHIKA S; KUMARESAN A (Innovare Journal Health Sciences, 2018)
Aim: To compare the relationship between Foot Type, Postural sway and Balance among the community dwelling older adult. Objective: 1. To find the correlation between foot type on static and dynamic balance among community dwelling older adults 2.To find the correlation between postural sway and foot type among community dwelling older adults. Methodology: 20 community dwelling older adults were included for the study based on inclusion and exclusion criteria. The subjects foot type was assessed using the navicular drop test. The subjects were classified into 3 different foot types: as pronated, neutral and supinated. After classifying the subject according to the foot type, they were measured for static and dynamic balance using Berg Balance Scale(BBS). For the same subjects, postural sway was assessed with Lord's Sway meter under 4 situations: 1. Standing on stable surface(floor) open eyes and 2. Standing on stable surface(floor) closed eyes, 3. Standing on unstable surface(foam) with eyes open and 4. Standing on unstable surface(foam) with eyes closed. The sway of older adult was recorded and analysed Result: There was strong correlation between pronated and anteroposterior sway in EO on unstable surface and between neutral and anteroposterior sway in EC standing on stable surface. There was moderate correlation between berg balance scale score and neutral foot type. Pronated and anteroposterior sway in EO standing on stable surface also showed moderate correlation. Conclusion: The results showed strong to moderate correlation between foot type, postural sway and balance, from this study it is clear that foot position affects the balance among older adults.